Refleksi Yuridis atas Penanganan Isu Pengungsi dalam Scope Penegakan Hukum Keimigrasian dan Relevansinya Terhadap Resistensi Kedaulatan Negara - Prawita, I Made Surya; Darmaja, I Nyoman Gede Adi; Yuda, I Wayan Rio Maha (Jurnal Ilmiah Wahana Pendidikan, 2024)
In facing the era of openness in various fields, aspects of sovereignty are asked to be at the forefront of defense which determines national security and state stability. The more sovereign a country is, the more logical consequences it has to face, both in terms of policy and juridical strengthening. Issues related to handling international refugees are a dilemmatic discussion when viewed from the legal basis that binds them and the attitude of Indonesia's foreign policy which did not ratify the 1951 convention and 1967 protocol on refugees. At least 145 countries have signed the convention and 146 countries have signed the protocol as a national legal instrument. The logical considerations that underlie Indonesia's stance have not ratified the two international legal instruments as an urgency that must be resolved. Even though the handling of refugee issues has been included in the National Human Rights Action Plan (RANHAM), in the 2021-2025 period the political will of the legislature shows that the urgency of handling refugees is not a priority study. This article will examine aspects of state sovereignty in overcoming potential law violations from an immigration perspective, which intersects with Indonesia's status as a transit country for refugees before being transferred to a third country hosting refugees.